Exergaming During Ramadan Intermittent Fasting Improve Body Composition as Well as Physiological and Psychological Responses to Physical Exercise in Adolescents With Obesity - Abedelmalek, Salma; Aloui, Khouloud; Denguezli Bouzgarou, Meriam; Adam, Halima; Souissi, Nizar; Chtourou, Hamdi (Frontiers in Nutrition, 2022)
The effects of exergaming on biochemical responses has been investigated; however, no data is available for this effect during Ramadan intermittent fasting (RIF). RIF is a daily fasting characterized by abstaining from eating and drinking from sunrise to sunset for 29-30 days. The purpose of this study was to investigate the effect of exergaming during RIF on body composition, physical performance and hematological parameters in overweight and adolescents with obesity. Twenty-four adolescents with obesity were divided into two groups [control group (CG), n=12, or cooperative sport exergaming group (EG), n=12: 45 min per session during five days per week)]. Participants completed a 6-min walking test (6MWT), a squat jump test and a 10m and a 30m sprint tests in four different occasions: before Ramadan (T0), the second week of Ramadan (T1), the fourth week of Ramadan (T2), and after Ramadan (T3). Blood pressure, rating of perceived exertion (RPE), body composition, central obesity index, dietary intake and profile of mood states (POMS) were, also, assessed over the four periods. The results showed that body weight, body mass index and body fat percentage were significantly lower at T2 compared to T0 and T1 in the EG. After RIF, body composition returned to the values recorded before RIF. The POMS score was significantly lower during T2 compared to T0, T1 and T3 in the EG. The vertical jump and the 6MWT distance were significantly higher (i) at T2 compared to T0, T1 and T3 in the EG and (ii) in EG compared to CG at T2. RPE was significantly lower (i) at T2 compared to T0, T1 and T3 in the EG and (ii) in EG compared to CG at T2. Blood pressure was lower during T2 compared to the other periods in EG. The EG experienced significant decreases in total cholesterol and triglycerides during T2. However, no significant changes between groups and periods was reported for all the other parameters. In conclusion, exergaming during RIF has a positive effect on body composition and physiological and psychological responses in adolescents with obesity.